PENGARUH DISTRAKSI MENONTON FILM KARTUN TERHADAP KENYAMANAN (NYERI) PADA ANAK USIA PRASEKOLAH YANG MENGALAMI PEMASANGAN INFUS DI RSUD TAMAN HUSADA BONTANG - Yeni Candra; Sutrisno Sutrisno; Amiruddin Amiruddin (Bajang Institute, 2023)
Background: The use of non-pharmacological techniques have significant effect on pain management in children. Combination of auditory (audio) distractions and visual (visual) distractions can be used to divertpatient's attention to the level of discomfort, anxiety and fear. Purpose:Determine effect of distraction from watching cartoon films on comfort (pain) in pre-school aged children who underwent infusion at Taman Husada Bontang Regional Hospital.Methode: This research uses quasi experimental designwith pre and post test approach without control design. Sample in this study was 35 children with IV drip installed in the Cempaka children's room. Using probability sampling technique with a total sampling method and Wilcoxon test.Result: Comfort level (pain) before and after watching cartoon films showed a decrease in pain from pre-test value to post-test value for 28 children out of a total of 35 preschool aged children. Resultsshow that there is an effect of distraction from watching cartoon films on comfort (pain) with p value = 0.000 ≤ 0.05. Conslusion: There is significant influence between distraction of watching cartoon films on the comfort (pain) of pre-school aged children who are undergoing IV drips at the Taman Husada Hospital, Bontang